2020
DOI: 10.1101/2020.12.20.20248580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Extension of State-Space SIR Model to Account for Underreporting- An Application to the COVID-19 transmission in California and Florida

Abstract: In the absence of sufficient testing capacity for COVID-19, a substantial number of infecteds are expected to remain undetected. Since the undetected cases are not quarantined, they are expected to transmit the infection at a much higher rate than their quarantined counterparts. That is, under the lack of extensive random testing, the actual prevalence and incidence of the SARS-CoV-2 infection may be entirely different from that being reported. Thus, it is imperative that the information on the percentage of u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Wu et al, 2020 [ 22 ] reported that the actual number of infections was estimated to be 3 to 20 times higher than the confirmed cases for various states of the United States of America. Lu et al, 2020 [ 23 ] showed that there were drastic cases of underreporting in many countries worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al, 2020 [ 22 ] reported that the actual number of infections was estimated to be 3 to 20 times higher than the confirmed cases for various states of the United States of America. Lu et al, 2020 [ 23 ] showed that there were drastic cases of underreporting in many countries worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…However, the significant problem was that many health systems underestimated the effect of the coronavirus (Ujvari, 2020). Soon, other aspects can be incorporated into the models, according to the disease cycle or socioeconomic aspect of the country, such as hospitalization dynamic (Bekker et al, 2023;Kozyreff, 2021), under-reporting cases (Chen et al, 2022;Deo & Grover, 2021), containment strategies (Das et al, 2021), age of individuals (Franco, 2021), macroeconomic impacts (Chan, 2022), outbreak recurrence (Muñoz-Fernández; Seoane; & Seoane-Sepúlveda, 2021), and other aspects. It is noted that the models are limited, as they work with possible assumptions about the spread of diseases.…”
Section: Introductionmentioning
confidence: 99%